Effect of high parity on occurrence of some fetal growth indices: a cohort study - Al-Farsi YM; Brooks DR; Werler MM; Cabral HJ; Al-Shafaee MA; Wallenburg HC (Dove Medical Press, 2012)
Yahya M Al-Farsi,1,2 Daniel R Brooks,2 Martha M Werler,2 Howard J Cabral,2 Mohammed A Al-Shafaee,1 Henk C Wallenburg31Department of Family Medicine and Public Health, College of Medicine and Health Sciences, Sultan Qaboos University, Muscat, Sultanate of Oman; 2Department of Epidemiology, School of Public Health, Boston University, Boston, MA, USA; 3Department of Obstetrics and Gynecology, College of Medicine and Health Sciences, Sultan Qaboos University, Muscat, Sultanate of OmanAbstract: The objective of this retrospective cohort study was to explore the potential causal relation between parity and fetal growth indices, including low birth weight (LBW), macrosomia, and prematurity. The study was nested on a community trial in a city in Oman. The study analyzed 1939 pregnancies among 479 participants. Of these, 944 pregnancies (48.7%) were high parity (≤5). Obtained newborns with outcomes of interest were as follows: 191 LBW, 34 macrosomic, and 69 premature. Associations were measured using multilevel logistic regression modeling. Compared to low parity (LP, defined as <5), high parity was found to be associated with less risk of LBW (relative risk [RR] = 0.76; 95% confidence interval [CI]: 0.44–1.1) and prematurity (RR = 0.82; 95% CI: 0.54–1.27), but greater risk of macrosomia (RR = 1.8; 95% CI: 1.2–2.4). This study provides evidence that with increasing parity, risks of LBW and prematurity decrease, while risk of macrosomia increases.Keywords: parity, fetal growth, low birth weight, macrosomia, prematurity, Oman